40Ar/39Ar constraints on the tectonic evolution of the central part of the Mesoproterozoic Sveconorwegian orogen. (January 2023) - Scheiber, Thomas; Viola, Giulio; Ganerød, Morgan; Bingen, Bernard
Abstract: Structural data combined with 40 Ar/ 39 Ar geochronology of hornblende, muscovite, biotite and plagioclase from 37 localities along three transects allow the time-constrained reconstruction of the Sveconorwegian deformation and cooling history of the Kongsberg lithotectonic unit and of the boundary zone to the adjacent Telemark lithotectonic unit in southern Norway. The Kongsberg lithotectonic unit consists of pervasively deformed, steeply dipping amphibolite-to granulite-facies gneisses, in which Mesoproterozoic 40 Ar/ 39 Ar ages of c. 1090-1070 Ma record cooling and exhumation. Ages scattering around 1000 Ma are interpreted as resetting of the K/Ar systems related to sinistral strike-slip deformation along c. N–S trending greenschist-to amphibolite facies shear zones and associated large-scale folding. Later, Neoproterozoic top-to-the-E normal shearing accommodated by the newly discovered Prestfoss detachment selectively exploiting the Kongsberg-Telemark boundary zone caused the exhumation of amphibolite-facies rocks of the Telemark lithotectonic unit and their juxtaposition against amphibolite-facies gneisses of the Kongsberg lithotectonic unit, which had cooled earlier in the orogenic history. 40 Ar/ 39 Ar ages constrain shearing and associated cooling to between c. 940 Ma and c. 900 Ma. Finally, a Silurian (420 ± 11 Ma) 40 Ar/ 39 Ar age may reflect localized partial to complete resetting due to Caledonian tectonics, and a Permian (288 ± 1 Ma) 40 Ar/ 39 Ar age constrains the intrusion of an Oslo Rift granite. Graphical abstract: Image 1 Highlights: Cooling of the Kongsberg lithotectonic unit is constrained to ca. 1090 and 1070 Ma. Sinistral shear deformation along subvertical shear zones was dated to ca. 1000 Ma. Structural analysis reveals the existence of the Prestfoss detachment in S Norway. Top-to-the-E extension along the Prestfoss detachment was dated to ca. 940-900 Ma.